Mesin Penyerut Lidi Kelapa Sawit Sistem Mekanis Bagi Kelompok Masyarakat Desa Timbang Lawan Bahorok - Eswanto, Eswanto; Hasan, Hanapi (Indonesia Berdaya, 2022)
In the process of separating leaves with sticks, the community in the Timbang Lawan Village area still uses human power and is done manually with a knife or machete. The solution is to make a stick shaver machine using a mechanical system with a capacity that is tailored to the needs of the user. The aim is to help increase the yield of palm oil sticks. The implementation method begins with examining the lack of technology and equipment in palm oil palm stick extraction, with stages 1). Follow-up surveys to partner locations to find out the work process of slashing and the output capacity to be achieved to meet market demand; 2). The design of the palm oil stick shaving machine uses mechanical energy; 3) Manufacture of palm oil stick crusher machine. 4) Test and install palm oil stick scraper machine before giving it to partners. 5) Socialization on how to maintain the shaver machine in Timbang Lawan Village. 6) handover of the shaver machine unit to the community group in Timbang Lawan Village. The results obtained where the shaved stick machine that has been completed is then handed over to the PKM partner. The machine can be operated and used by partners, where the production of palm oil sticks obtained increases by more than 100% or has a capacity of 15 kg/hour sticks, compared to manual which only gets 2 to 5 kg/3 hours of clean sticks